EFFECT OF HOUSEHOLD POVERTY ON WOODFUEL CONSUMPTION IN SUB SAHARAN AFRICAN COUNTRIES: EVIDENCE FROM SYSTEM GMM MODEL - SHEHU, HABU; YAHAYA, YAKUBU; AUWAL, YAHAYA; UMAR, BALA (JOURNAL OF ECONOMICS AND ALLIED RESEARCH, 2025)
This study aims to investigate the effect of household poverty on woodfuel consumption in Sub-Saharan African countries by using a panel data set of 43 countries spanning from 2011 to 2019. Generalized Method of Moment (GMM) was employed to analyze the data. The finding of the study reveals a strong positive association between household poverty and woodfuel consumption, with a 1% increase in household poverty increasing woodfuel consumption by 65.1%. The study further reveals that clean fuel and technology, dependency ratio, and female labor participation were significant determinants of woodfuel consumption in Sub-Saharan African countries. These findings have significant implications for the health and economic well-being of the region's population. Sub-Saharan African governments, non-governmental organizations, donor agencies, and foundations are urged to make clean cooking energy, such as electricity, gas, and solar, more readily available and affordable to households, easing the transition from wood fuel to cleaner fuels.